Defining Quality Indicators for Breast Device Surgery: Using Registries for Global Benchmarking. Issue 8 (August 2019) - Begum, Husna; Vishwanath, Swarna; Merenda, Michelle; Tacey, Mark; Dean, Nicola; Elder, Elisabeth; Mureau, Marc; Bezic, Ron; Carter, Pamela; Cooter, Rodney D.; Deva, Anand; Earnest, Arul; et al.
Abstract : Background: Breast device registries monitor devices encompassing breast implants, tissue expanders and dermal matrices, and the quality of care and patient outcomes for breast device surgery. Defining a standard set of quality indicators and risk adjustment factors will enable consistency and adjustment for case-mix in benchmarking quality of care across breast implant registries. This study aimed to develop a set of quality indicators to enable assessment and reporting of quality of care for breast device surgery which can be applied globally. Methods: A scoping literature review was undertaken, and potential quality indicators were identified. Consensus on the final list of quality indicators was obtained using a modified Delphi approach. This process involved a series of online surveys, and teleconferences over 6 months. The Delphi panel included participants from various countries and representation from surgical specialty groups including breast and general surgeons, plastic and reconstructive surgeons, cosmetic surgeons, a breast-care nurse, a consumer, a devices regulator (Therapeutic Goods Administration), and a biostatistician. A total of 12 candidate indicators were proposed: Intraoperative antibiotic wash, intraoperative antiseptic wash, preoperative antibiotics, nipple shields, surgical plane, volume of implant, funnels, immediate versus delayed reconstruction, time to revision, reoperation due to complications, patient satisfaction, and volume of activity. Results: Three of the 12 proposed indicators were endorsed by the panel: preoperative intravenous antibiotics, reoperation due to complication, and patient reported outcome measures. Conclusion: The 3 endorsed quality indicator measures will enable breast device registries to standardize benchmarking of care internationally for patients undergoing breast device surgery. Abstract : Supplemental Digital Content is available in the text.